Label Pintar untuk Pemonitoran Kesegaran Daging Ayam pada Kemasan - Novialda Nitiyacassari; Bambang Kuswandi; Dian Agung Pangaribowo (Pustaka Kesehatan, 2021)
Chicken meat is one of the commodities consumed by most Indonesian people and has a pH range of 5,5 – 6,0. The smart label has been applied as a chicken meat freshness detector. As dual indicator freshness, two pH indicators have been used, i.e., bromothymol blue (BTB) and methyl red (MR). The objective of this research was to determine chicken meat freshness using a smart label at room temperature. The color change of the smart label was examined by ImageJ software to determine freshness degree using the mean RGB value. The chicken meat was examined every 2 hours for pH and TVB analysis during the 24 hours storage at room temperature. The result showed that color indicator would change according to chicken meat freshness, BTB turned from yellow to blue (mean RGB 210,591 ± 0,376), and MR turned from red to yellow (mean RGB 208,146 ± 0,390). Chicken meat freshness at room temperature decreased as pH increase from 5,68 to 6,11 along with a color change of smart label. Furthermore, the color would change when 0.022 %N of TVB has been reached. Therefore, chicken meat freshness can be determined by using a smart label based on a dual indicator of bromothymol blue and methyl red at room temperature.